Configurational paths to turnover intention among primary public health workers in Liaoning Province, China: a fuzzy-set qualitative comparative analysis - Xueying Li; Chenxin Yang; Libing Liu; Yuanlu Ding; Jianchun Xue; Jiani He; Hui Wu; Li Liu (BMC, 2024)
Abstract Background A stable public health workforce plays an indispensable role in the realization of the goal of health for all. However, there is an exodus of public health workers from the Centers for Disease Control and Prevention (CDC). Given the limited evidence on the mechanisms shaping turnover intention (TI) among public health workers, the study aims to investigate the triggering mechanisms of high and low turnover intention by combining job demands, job resources, and personal resources through a set theory perspective based on the Job-Demand-Resources (JD-R) model. Methods The cross-sectional study was conducted from September 7 to 18, 2020 at district (county) level CDC in Liaoning Province, China. A total of 584 public health professionals were included. Overcommitment, effort, social respect, occupational identity, job rewards, self-efficacy, and psychological resilience were included in the study as configuration factors. The data were gathered through an online questionnaire and were analyzed using multiple regression and fuzzy-set Qualitative Comparative Analysis (fsQCA). Results Social respect (B = -0.682, P < 0.001), occupational identity (B = -0.168, P < 0.001), and effort (B = 0.114, P < 0.001) were associated with turnover intention. Five configurations for high turnover intention and five for low turnover intention were obtained through the fsQCA, with occupational identity and effort playing an essential role in all pathways. Moreover, the configurations for low turnover intention are not the antithesis of the configurations for high turnover intention. Conclusion Managers should synthesize the combined effects of factors when implementing interventions and formulating policies. Given the vital role of occupational identity and effort, mechanisms for the rational distribution of work to avoid excessive efforts and measures to promote occupational identity should be implemented to reduce the turnover intentions of primary public health workers and encourage their intention to stay.